1995
DOI: 10.3109/01460869509080961
|View full text |Cite
|
Sign up to set email alerts
|

Communication and Control: Parent, Child, and Health Care Professional Interactions During Painful Procedures

Abstract: Through use of a qualitative ethological approach, observations of 17 children who were undergoing 44 painful procedures during cancer diagnosis or treatment were videotaped and analyzed. The children, aged 4 to 18 years, were part of a larger study testing the effectiveness of nonpharmacologic pain management techniques. Analysis of the videotaped observations revealed that several distinct patterns of conversation between caregivers, parents, and children varied greatly among situations. Both child-centered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 8 publications
1
23
0
2
Order By: Relevance
“…Our findings are consistent with the results of other studies indicating that parents need to be given a clear role, guidance, and coaching to maximize their presence in facilitating a child's coping (Bauchner, 1991;Broome, 1990Broome, , 2000Cohen et al, 1997;Colaizzo & Tesler, 1994;Fanurik, Koh, Schmitz, & Brown, 1997;Goldberger et al 1990;Kristensson-Hallstron, 1999;Manne et al, 1994;Rusy & Weisman, 2000). Moreover, children's distress (Naber, Broome, & Rehwaldt, 1995) and parents' anxiety (Bauchner et al, 1996) have been found to be reduced when parents receive guidance on providing positive parental attention and physical closeness with their child.…”
Section: Implications For Practicesupporting
confidence: 95%
“…Our findings are consistent with the results of other studies indicating that parents need to be given a clear role, guidance, and coaching to maximize their presence in facilitating a child's coping (Bauchner, 1991;Broome, 1990Broome, , 2000Cohen et al, 1997;Colaizzo & Tesler, 1994;Fanurik, Koh, Schmitz, & Brown, 1997;Goldberger et al 1990;Kristensson-Hallstron, 1999;Manne et al, 1994;Rusy & Weisman, 2000). Moreover, children's distress (Naber, Broome, & Rehwaldt, 1995) and parents' anxiety (Bauchner et al, 1996) have been found to be reduced when parents receive guidance on providing positive parental attention and physical closeness with their child.…”
Section: Implications For Practicesupporting
confidence: 95%
“…[16] Ağrılı işlemler sırasında ebeveynin çocuğunun yanında olması çocuğu için yapılan uygulamayı görmesini sağ-lar ve aile üyeleri ile sağlık personeli arasında güçlü bir bağ kurulmasına da yardımcı olur ve çocuğun stresi azalıp işleme uyumunu artırır. [17,18] Ebeveynlerin ağrılı işlemler sırasında çocuklarıyla birlikte olmasının yararları yapılan çalışmalarla ortaya konmuş olmasına karşın sağlık personeli ağrılı işlemler sıra-sında ebeveynlerin çocuklarıyla birlikte olması konusunda bazı tereddütler yaşamaktadırlar. [6] Hastanelerde oluşturulacak politika ve prosedürle-rin aile merkezli olabilmesi ve ağrılı işlemlerde ço-cukların yanında kalabilmeleri için gerekli politika ve prosedürlerin geliştirilebilmesi için öncelikle sağlık personelinin konu ile ilgili görüşlerinin belirlenmesi gerekmektedir.…”
Section: Introductionunclassified
“…In the literature reviewed, an extensive amount has been written on adult communication during painful procedures and child behavioral distress (Blount et al, 1989;Blount, Sturges, & Power, 1990;Blount et al, 2000;Cline et al, 2006;Cohen et al, 2002;Dahlquist et al, 2001;Fanurik, Koh, & Schmitz, 2000;Frank, Blount, Smith, Manimala, & Martin, 1995;Gelfand & Dahlquist, 2003;Jay, 1988;Manimala, Blount, & Cohen, 2000;Manne et al, 1992;McCarthy et al, 2010;Naber, Halstead, Broome, & Rehwaldt, 1995;Slifer et al, 2011;Sweet & McGrath, 1998;Vessey, Carlson, & McGill, 1994). Pediatric procedural distress has been a topic of focus mainly in the area of pediatric oncology specific to lumbar punctures, bone marrow aspirations (Blount et al, 1989;Blount et al, 1990;Blount et al, 2000;Cline et al, 2006;Dahlquist et al, 2001;Gelfand & Dalquist, 2003;Naber et al, 1995) and needle procedures that include venipuncture, immunizations, and intravenous catheter insertion in the inpatient and outpatient setting (Cohen et al, 2002;Fanurik et al, 2000;Frank et al, 1995;Manimala et al, 2000;Manne et al, 1992;McCarthy et al, 2010;Slifer et al, 2011;Sweet & McGrath, 1998;Vessey et al, 1994).…”
Section: Communication Related To Comfort In the Emergency Departmentmentioning
confidence: 99%
“…Pediatric procedural distress has been a topic of focus mainly in the area of pediatric oncology specific to lumbar punctures, bone marrow aspirations (Blount et al, 1989;Blount et al, 1990;Blount et al, 2000;Cline et al, 2006;Dahlquist et al, 2001;Gelfand & Dalquist, 2003;Naber et al, 1995) and needle procedures that include venipuncture, immunizations, and intravenous catheter insertion in the inpatient and outpatient setting (Cohen et al, 2002;Fanurik et al, 2000;Frank et al, 1995;Manimala et al, 2000;Manne et al, 1992;McCarthy et al, 2010;Slifer et al, 2011;Sweet & McGrath, 1998;Vessey et al, 1994).…”
Section: Communication Related To Comfort In the Emergency Departmentmentioning
confidence: 99%
See 1 more Smart Citation